Financial Innovations and Performance of Savings and Credit Co-operatives Societies in Kirinyaga County, Kenya - Ngure, Francis (University of Embu, 2017)
SACCOS are the main drivers of economic and social development in rural areas of developing countries. In Kenya 81% of the population rely on the SACCOs to access financial services. However the use of SACCOs by Kenyans as a financial service provider has been declining. The SACCOs are faced with challenges of survival due to decline of members. The decline is attributed to the competition from other financial institutions which have embraced financial innovations. The study therefore sought to investigate the effect of financial innovations on performance of SACCOs in Kenya. The study adopted cross sectional descriptive survey research design. The target population was 60 SACCOs registered by SASRA to operate in Kirinyaga County. Stratified simple random sampling technique was used to obtain the sample size of fifty two SACCOs for the study. Primary data was collected using self-administered questionnaires while secondary data was obtained from audited financial statements. A pilot test was conducted to ascertain the validity and reliability of questionnaire. The Cronbach’s alpha coefficient was used for reliability test while the content validity technique was used in validating the research instruments. Primary and secondary data was analyzed using SPSS version. The findings of the study revealed that financial innovations had a positive relationship with financial performance of SACCOs in Kirinyaga County. SACCOs should therefore embrace financial innovations which include product innovations, process innovations and institutional innovations in order to improve their financial performance. SACCOs should introduce new deposit accounts in order to increase the amount of deposits. The SACCOs should also introduce credit and debit cards in order to increase their revenue. Similarly, the SACCOs should introduce electronic fund transfer in order to increase commission fee based income. The institution should automate their operations in order to enhance efficiency. In addition, mobile banking, cashless and paperless services should be introduced in order to reduce operation costs. The firms should also change their management systems and come up with policies that will facilitate restructuring of their operations in order to improve service delivery to their customers.